Famine and disease in economic history: A summary introduction - Guido Alfani; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2018)
Understanding mortality crises is an important part of understanding some fundamental aspects of preindustrial economies. Understanding the processes leading to their decline and the associated improvements in living standards and life expectancy is a precondition for knowing what is needed to prevent the reemergence of widespread famine and lethal infectious disease. This short paper introduces a field in which policy makers and economists need to carefully consider the past, before making assumptions about the future.
Keywords: N10; 330; famine; disease; epidemics; economic history